The interplay of self-esteem, self-discipline, and financial satisfaction in shaping the well-being of remote workers in Lebanon - El Khoury, Samar (Technium Social Sciences Journal, 2025)
Background: The concept of subjective well-being is critical to mental health and productivity, particularly in remote work settings. With the acceleration of remote work adoption worldwide, the interplay between personal attributes and well-being has garnered significant interest in recent years. This study explores key determinants influencing the well-being of remote workers in Lebanon’s digital industry. Objective: To examine the relationship between self-esteem, self-discipline, financial satisfaction, and the overall well-being of remote workers. Methods and Materials: A quantitative cross-sectional study was conducted using an online survey completed by 293 participants recruited through professional networks and digital platforms. Key scales included the Rosenberg Self-Esteem Scale, the Brief Self-Control Scale, and a financial satisfaction measure. The 14-item General Well-Being Scale assessed overall well-being. Statistical analysis, including bivariate and multivariate regression, was performed using SPSS 27.0. Results: The findings revealed strong positive correlations between self-esteem (r = 0.422), self-discipline (r = 0.312), and financial satisfaction (r = 0.326) with well-being. Multivariate regression highlighted self-esteem (β = 0.66), financial satisfaction (β = 1.43), and income above 1,000 as significant predictors of well-being. Marital status and job security also influenced well-being, with "married with children" reporting challenges compared to single respondents. Conclusion: This study underscores the importance of psychological and financial factors in shaping the well-being of remote workers. Enhancing self-esteem, promoting financial security, and addressing job satisfaction are critical for improving remote work experiences.